Effect of structural disorder on the thermal transport properties of amorphous materials - PNG, Edwin WeiChen (2016)
There is an ever increasing need to find alternative sources of energy in this world as oil supply becomes increasingly diminished, and because of the environmental problems. Thermoelectric devices is an alternative solution as it can be powered on waste heat. Thermoelectric materials come in di fferent forms and structures. One reason for that is to suppress phonon thermal conductivity, which raises the performance. The effect of various forms of structural disorder on thermal conductivity is studied, fi rst in a binary Lennard-Jones model, and then in a system of hard spheres in the regime of the jamming transition. A competing effect between thermal conductivity and electrical conductivity that is important to thermoelectric efficiency is investigated in the hard sphere model.